eHealth literacy in digital era: trends of development - Sobolieva-Tereshchenko, Olena (Management and Entrepreneurship: Trends of Development, 2023)
The study supplies a conceptual framework for the development and use of eHealth literacy in digital health management, as well as in government and international eHealth management activities. This study aims to gain a deep understanding and analysis of eHealth literacy measurement trends through a systematic review and analysis of articles published (from January 2006 to January 2023) in PubMed, Web of Science, and Scopus. There are fifteen original and high-quality validation studies found in the systematic literature review on measuring eHealth literacy. The study found three stages in the development of eHealth literacy measurement, which are characterized by a suitable set of skills. eHLS-Web 3.0 has high internal and external consistency scores, and eHEALS and HLS-EU-Q-16 have higher reliability for the basic development of an international eHealth literacy measurement instrument in digital health management. This study is a research program to guide future study and help knowledge accumulation and creation on eHealth Literacy instruments and their implementation in digital health management. The result of the study was supplied eHealth instruments for the implementation and training of eHealth Literacy in information systems. Future research themes in eHealth literacy will include the standardization of eHealth assessment instruments and the development of health strategies for different target audiences of various levels of management. And, to encourage further progress in the development of methodology and the application of eHealth literacy in information systems. JEL Classification: I11, I18, H51